ASTRONOMICAL INTERPRETATION OF EARLY PRAYER TIMES (Study of Differences in Determination of Early Prayer Times From The Text and Astronomical Prespective) - Rifki Hasan Hasan (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
Theoretically the prayer times have been determined by the Koran and Sunnah through the phenomenon of the movement of the sun. Based on the instructions of the Koran and the Sunnah there are various nashes that seem to contradict one another. For example, in the determination of early Fajr time, nashexpresses with some terminologhy, for example, ghalas, isfar, and ishbah. This needs to be defined practically in astronomical rules, making it easier for us to carry out worship. This paper will describe the meaning of prayer times from the language of the Koran and Sunnah into astronomical rules, so that prayer times can be easily reckoned and determined, without having to change the phenomenon of the sun every time it will perform prayers. This paper will include the debate of scholars in interpreting sharia in astronomical rules, so that this paper is not only doctrinal, but invites us to think more creatively in determining prayer times.